MRI macromolecular contrast agents as indicators of changed tumor blood flow - Ivanuša, Teodora (Radiology and oncology (Ljubljana), 2001)
Background. A rapid mapping technique derived from dynamic contrast enhanced MRI data was used to identify and characterize reduction of blood flow in fibrosarcoma SA-1 tumors treated either by application of electric pulses or vinblastine. Materials and methods. Tissue permeability surface area product (PS) and fractional blood volume (BV) were calculated on a pixel-by-pixel basis using dynamic MRI intensity data after administration of gadomer - 17 orpolylysine-Gd-DTPA; prototypic macromolecular contrast agents designed for blood pool enhancement. PS and BV values of untreated tumors were compared to those of tumors treated by local application of 8 electric pulses (amplitude/distance ratio, 1300 V/cm; duration, 100 us, frequency, 1 Hz) percutaneously to the tumor or by systemic administration of vinblastine (2.5 mg/kg). Results. Both treatments transiently, but significantly reduced tumor blood flow, application of electric pulses to the tumors being by 40% more effective in reducing tumor blood flow than systemic administration of vinblastine. PS and BV values derived with polylysine-Gd-DTPA-enhanced MRI were lower compared to those with gadomer-17, due to larger molecular size. Interestingly, Gd-DTPA-enhanced MRI did not show any significant changes of PSand BV between untreated and treated tumors. Conclusion. This study demonstrates that dynamic contrast enhanced MRI can be effectively used to qualitatively monitor tumor blood flow, and quantitatively by means of BV and PS.
Keywords: Blood supply; Contrast media; diagnostika; Drug delivery systems; Electroporation; Gadolinium; jedrska magnetna resonanca; Magnetic resonance imaging; Mice; neoplasm; rak (medicina); Sarcoma, experimental; Therapy; tumor; Vinblastine